2016
DOI: 10.1016/j.ydbio.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory embryonic response to allele-specific inactivation of the murine X-linked gene Hcfc1

Abstract: Early in female mammalian embryonic development, cells randomly inactivate one of the two X chromosomes to achieve overall equal inactivation of parental X-linked alleles. Hcfc1 is a highly conserved X-linked mouse gene that encodes HCF-1 - a transcriptional co-regulator implicated in cell proliferation in tissue culture cells. By generating a Cre-recombinase inducible Hcfc1 knock-out (Hcfc1(lox)) allele in mice, we have probed the role of HCF-1 in actively proliferating embryonic cells and in cell-cycle re-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…Fig. 1A1) (Minocha et al , ), but with a progressive reduction in relative HCF‐1 protein levels with age (Supp. Fig.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Fig. 1A1) (Minocha et al , ), but with a progressive reduction in relative HCF‐1 protein levels with age (Supp. Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The human HCFC1 and mouse Hcfc1 genes are highly expressed in actively dividing tissue culture cells, and in embryonic and placental tissues and in adult tissues (Wilson et al , ; Frattini et al , ; Kristie, ; Huang et al , ; Minocha et al , ). Previously, using a well‐characterized antibody generating little to no non‐specific reactivity (H12), we have shown that HCF‐1 is ubiquitous and predominantly nuclear in E6.5‐to‐E12.5 embryos, postnatal day 0 (P0) brains, and 10‐week‐old young adult brains (Minocha et al , ). Here, we further investigated in detail the cellular and subcellular localization of HCF‐1 in the early mouse brain by immunostaining wild‐type C57BL/6 postnatal day 0 (P0) brains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations